Cross-cultural adaptation and psychometric validation of the Spanish version of the SBAR-LA rubric for structured communication in nursing simulation - Jaime Carballedo-Pulido; Mariona Farrés-Tarafa; Juan Roldán-Merino; Marta Berenguer-Poblet; Montserrat Girabent-Farrés; Carla Otero-Arús; Susana Santos-Ruiz (PLoS ONE, 2025)
Background Although the SBAR framework is widely used in clinical and educational settings, there is a lack of validated Spanish-language tools that objectively assess its use by students in simulation. The adaptation and validation of the SBAR-LA rubric address this gap and provide a resource for training and evaluating structured communication. Objective To conduct the cross-cultural adaptation and psychometric validation of the SBAR-LA rubric in Spanish for assessing structured communication skills in undergraduate nursing students during clinical simulation. Methods A two-phase cross-sectional psychometric validation study was conducted. Phase one involved cross-cultural adaptation, including forward and backward translation, expert panel review, and cognitive debriefing with nursing students. Phase two assessed inter-rater reliability using Krippendorff’s alpha based on 97 performance evaluations obtained in different simulation scenarios. The SBAR-LA-Sp rubric contains 10 dichotomous items across the four SBAR dimensions. Results The Spanish version of the SBAR-LA rubric demonstrated excellent inter-rater reliability, with a Krippendorff’s alpha of 0.933 (95% CI: 0.905–0.956). Internal consistency and agreement between raters were also high, confirming the instrument’s robustness. Conclusions The Spanish version of the SBAR-LA rubric provides an objective measure of structured communication in nursing simulation. The findings support its use in academic training. Further research is needed to examine its effect on learning outcomes.